(3eUHGM GdRLGLIs - (3CMeO Hf CHj ESeGYjd Hf Sdje Hf bGjeGR GdHhUjQj, TgGH GdOjf CHhGdYHGS GdHhUjQj,J (B840 (3g` s ((3eMeO hdO GdeUfa s)
(3ChdgG (B:s
(3GdMeO ddg GdPi TQafG HeG NGWHfG Hg ef cdGeI GdeLjO hHYO abO GSJNQJ Gddg YR hLd ai EaQGO RhGFO ddEeGe GdMGaX CHj YHO Gddg eMeO Hf jRjO Hf eGLI GdbRhjfi s
(3BNQgG (B:s
(3hgPG BNQ eUHGM GdRLGLI ai RhGFO GHf eGLI hGddg JYGdi jfaY Hg LGeYI hbGQFI hef fXQ ajg s
(3ajg ef GdCMGOjK GdUMjMI hGdVYjaI (B1530 (3MOjK (B"s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B110s
(3JHUQGJ GdCUd (B:s
Keywords: (3eJaQbGJs